Pregnancy in the non-communicating rudimentary horn of a unicornuate Uterus: a case report of Saghez - Jamileh Salavati; Fariba Ebtekar; Vajiheh Baghi; Bakhtyar Moslemi; Reza Ghanei Gheshlagh (Kurdistan University of Medical Sciences, 2018)
Background and Aim: Pregnancy in the Non-communicating Rudimentary Horn of a Unicornuate Uterus is very rare and dangerous that often after uterine rupture, hemorrhagic shock or peritoneal hematomas detected. Case presentation: In this report, a 36-year-old woman with abdominal pain and gestational age of 17 weeks with the pre-shock was admitted to the hospital. The patient was transferred to the operating room because of abdominal bleeding and a vertical incision was made under spinal anesthesia. Horns evolved apart without causing damage to the uterus. Conclusion: Pregnancy in a rudimentary horn carries severe risk to the mothers. It is recommended that immediately surgery in a rudimentary horn is made even if unruptured.